The Influence of Genre Pedagogical and Content and Language Integrated Learning on Elementary Students’ Writing Skills (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The objectives of this study are (1) to find out and to present the evidence whether the pedagogical model of the genre affects the writing skills of elementary school students, (2) to know and present the evidence whether Content and Language Integrated Learning (CLIL) affects the writing skills of elementary school students, (3) to know and explain evidence whether the genre pedagogical model and Content and Language Integrated Learning (CLIL) jointly influence the writing skills of elementary school students. This research is a Pre-Experimental Design with One Group Pretest-Posttest Design. In this design, there is only one class that will be analyzed and measure the extent of students' writing skills before and after treatment. The results of the study are proven (1) that genre pedagogical model has a positive and significant effect on the writing skills of grade 5 elementary school students, (2) that the Content and Language Integrated Learning (CLIL) has a positive and significant effect on the writing skills of grade 5 elementary school students, (3) that the genre pedagogical model and Content and Language Integrated Learning (CLIL) jointly influence the writing skills of grade 5 elementary school students.